ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA MATERI LUAS PERMUKAAN DAN VOLUME BANGUN RUANG SISI DATAR - Khoirunnisa, Syifa; Sulhan, Sulhan; Kalsum, Umi; Timbu, Dorkas Lali; Ngongo, Oktavianus Bulu; Ambarawati, Mika (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2020)
Most students consider mathematics as a difficult and confusing subject of the many subjects, solid geometry is one of the mathematical subjects considered by students to be the most difficult to understand. Therefore a study was conducted on the difficulties of students in completing the material in solid geometry. The purpose of this study is to describe the difficulty of students in solving mathematical problems in the material surface area and volume of the solid geometry with flat side, especially rectangular solid. This research is a descriptive qualitative research. Based on research that has been done, it is known that students have difficulty understanding concepts and definitions, difficulty applying formulas, and difficulty in calculations.